THE CHROMIUM (Cr) CONTENT IN WATER AND IN THE TISSUE OF MUD CRAB (Scylla serrata Forskal.) IN THE BRACKISHWATER PONDS AROUND BABON RIVER ESTUARY - Nanik Heru Suprapti; Lachmuddin Sya’rani; Sutrisno Anggoro (JOURNAL OF COASTAL DEVELOPMENT, 2012)
One of the problems that faced by marine aquacultures is the presence of industrial development in the nearby areas. The research aim was to study Chromium (Cr) content in the waters and in the crabs (Scylla serrata) in Brackishwater ponds around Babon River estuary of coastal areas Semarang, in Central Java. Systematical random sampling was used in this study. Analysis of Cr content in the water was compared to water quality criteria by Indonesian Ministry of Environmental. Analysis of Cr content in the tissue of crab was based on Manual Criteria by United States Food and Drug Administration (U.S. FDA). Bioconcentration Factor was used to analyse the accumulative of Chromium content. The results showed that Chromium content in the water was 0,078 ppm (dry season) and 0,065 ppm (rainy season), respectively. Chromium content in the tissue of mud crab (Scylla serrata) was 5,237 ppm (dry season) and 4,848 ppm (rainy season) and was under of maximum level recommended (12 ppm). The Bio Concentration Factor (BCF) of Cr content has low accumulative characteristic (<100).